2011
DOI: 10.1161/atvbaha.110.219980
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Apelin-APJ System Worsens Hypoxia-Induced Pulmonary Hypertension

Abstract: Objective The G-protein–coupled receptor APJ and its ligand apelin are highly expressed in the pulmonary vasculature, but their function in this vascular bed is unclear. We hypothesized that disruption of apelin signaling would lead to worsening of the vascular remodeling associated with pulmonary hypertension (PH). Methods and Results We found that apelin-null mice developed more severe PH compared with wild-type mice when exposed to chronic hypoxia. Microcomputed tomography of the pulmonary arteries demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
187
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(196 citation statements)
references
References 46 publications
8
187
0
1
Order By: Relevance
“…In addition to the autocrine functions of apelin, it displays a paracrine effect by attenuating the response of PASMCs to growth factors and by promoting apoptosis. These findings support the beneficial effect of apelin on cardiac function in rats with PAH (28), underscore the adverse impact of its loss on the severity of PAH (29), and make apelin an attractive pharmacological target for the treatment of PAH.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition to the autocrine functions of apelin, it displays a paracrine effect by attenuating the response of PASMCs to growth factors and by promoting apoptosis. These findings support the beneficial effect of apelin on cardiac function in rats with PAH (28), underscore the adverse impact of its loss on the severity of PAH (29), and make apelin an attractive pharmacological target for the treatment of PAH.…”
Section: Discussionsupporting
confidence: 83%
“…Circulating ape- lin levels are decreased in IPAH patients (27), and apelin administration improves RV function in the monocrotaline rat model of PAH (28). In addition, loss of apelin worsens hypoxia-induced pulmonary hypertension in association with decreased number and enhanced muscularization of peripheral arteries (29).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Another benefitial effect of apelin may be mitigation of angiotensin-2 induced cardiac fibrosis 72 and ischemia induced apoptosis of cardiomycytes 73 . Patients with pulmonary arterial hypertension (PAH) have lower plasma levels and reduced apelin expression in lung endothelial cells 74 . Chronic therapy with apelin alleviates the pulmonary hypertension and increases the contractility of failing right ventricle in mice with pulmonary hypertension induced by monocrotalin and hypoxia 68 .…”
Section: Apelinmentioning
confidence: 99%
“…Previous studies indicated that apelin-13 is able to regulate glucose and lipid metabolism (12,13) via the activation of AMPK signaling. The disruption of apelin-13 signaling can increase the hypoxia-induced pulmonary hypertension mediated by decreased activation of AMPK and endothelial nitric oxide synthase (eNOS) (14). In addition, as protein kinase Akt/protein kinase B (Akt) signaling participates in vascular homeostasis and angiogenesis (15,16), it can also phosphorylate eNOS (17), resulting in NO production and subsequently leading to the regulation of vasomotor responses.…”
Section: Introductionmentioning
confidence: 99%